Morphological and Morphogenetic Characteristics of Dark Gray Soils (in the Example of theBakhmal District, Jizzakh Region) (Texas Journal of Agriculture and Biological Sciences, 2025)
This study investigates the morphological and morphogenetic characteristics of dark gray soils developed under natural conditions in the Bakhmal district of the Jizzakh region, Uzbekistan. The research was conducted on uncultivated dryland dark gray soils formed on deluvial–proluvial and loess parent materials within a semi-arid climate and a complex geomorphological setting. Field investigations included the description of soil horizons, determination of humus horizon thickness, and analysis of carbonate accumulation patterns. Laboratory analysis complemented field data to assess the physical structure and textural composition of the profiles